Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve for [tex]\((g \circ f)(3)\)[/tex], we need to follow these steps:
1. Find [tex]\( f(3) \)[/tex]:
- We are given the function [tex]\( f(x) = 4x + 2 \)[/tex].
- Substitute [tex]\( x = 3 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(3) = 4(3) + 2 = 12 + 2 = 14 \][/tex]
2. Now, use the result of [tex]\( f(3) \)[/tex] to find [tex]\( g(f(3)) \)[/tex]:
- We found [tex]\( f(3) = 14 \)[/tex].
- Next, we are given the function [tex]\( g(x) = x^2 - 2x - 5 \)[/tex].
- Substitute [tex]\( x = 14 \)[/tex] into the function [tex]\( g(x) \)[/tex]:
[tex]\[ g(14) = 14^2 - 2(14) - 5 \][/tex]
3. Calculate [tex]\( g(14) \)[/tex]:
- First, compute [tex]\( 14^2 \)[/tex]:
[tex]\[ 14^2 = 196 \][/tex]
- Then, compute [tex]\( 2(14) \)[/tex]:
[tex]\[ 2(14) = 28 \][/tex]
- Now, substitute these values back into [tex]\( g(14) \)[/tex]:
[tex]\[ g(14) = 196 - 28 - 5 = 168 - 5 = 163 \][/tex]
Therefore, the value of [tex]\((g \circ f)(3)\)[/tex] is [tex]\(163\)[/tex].
1. Find [tex]\( f(3) \)[/tex]:
- We are given the function [tex]\( f(x) = 4x + 2 \)[/tex].
- Substitute [tex]\( x = 3 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(3) = 4(3) + 2 = 12 + 2 = 14 \][/tex]
2. Now, use the result of [tex]\( f(3) \)[/tex] to find [tex]\( g(f(3)) \)[/tex]:
- We found [tex]\( f(3) = 14 \)[/tex].
- Next, we are given the function [tex]\( g(x) = x^2 - 2x - 5 \)[/tex].
- Substitute [tex]\( x = 14 \)[/tex] into the function [tex]\( g(x) \)[/tex]:
[tex]\[ g(14) = 14^2 - 2(14) - 5 \][/tex]
3. Calculate [tex]\( g(14) \)[/tex]:
- First, compute [tex]\( 14^2 \)[/tex]:
[tex]\[ 14^2 = 196 \][/tex]
- Then, compute [tex]\( 2(14) \)[/tex]:
[tex]\[ 2(14) = 28 \][/tex]
- Now, substitute these values back into [tex]\( g(14) \)[/tex]:
[tex]\[ g(14) = 196 - 28 - 5 = 168 - 5 = 163 \][/tex]
Therefore, the value of [tex]\((g \circ f)(3)\)[/tex] is [tex]\(163\)[/tex].
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.